2021
DOI: 10.1093/molehr/gaab050
|View full text |Cite
|
Sign up to set email alerts
|

Integrated stress response control of granulosa cell translation and proliferation during normal ovarian follicle development

Abstract: Mechanisms that directly control mammalian ovarian primordial follicle (PF) growth activation and the selection of individual follicles for survival are largely unknown. Follicle cells produce factors that can act as potent inducers of cellular stress during normal function. Consistent with this, we show here that normal, untreated ovarian cells, including pre-granulosa cells of dormant PFs, express phenotype and protein markers of the activated integrated stress response (ISR), including stress-specific prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 82 publications
3
20
0
Order By: Relevance
“…We have generated immunofluorescence data that shows variable levels of the core ISR regulatory factor P-eIF2 α in mouse PF pregranulosa cells and oocytes (Hagen-Lillevik, submitted, preprint available at https://www.researchsquare.com/article/rs-1682172/v1). However, despite our prior detection of P-eIF2 α in human nongrowing follicles (20), a study comparing P-eIF2 α levels in nongrowing follicles in multiple replicate human ovary specimens has not yet been performed. While it is highly likely that regional differences in stress and damage occur similarly between the mouse and human ovary, it may be that mechanisms that respond to these dynamic local conditions differ between the species.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…We have generated immunofluorescence data that shows variable levels of the core ISR regulatory factor P-eIF2 α in mouse PF pregranulosa cells and oocytes (Hagen-Lillevik, submitted, preprint available at https://www.researchsquare.com/article/rs-1682172/v1). However, despite our prior detection of P-eIF2 α in human nongrowing follicles (20), a study comparing P-eIF2 α levels in nongrowing follicles in multiple replicate human ovary specimens has not yet been performed. While it is highly likely that regional differences in stress and damage occur similarly between the mouse and human ovary, it may be that mechanisms that respond to these dynamic local conditions differ between the species.…”
Section: Discussionmentioning
confidence: 98%
“…We reasoned that if the biological mechanisms at work in individual PFs that dictate the probabilities of arrest or growth over time can be clarified, we might be able to predict and simulate PFGA over time in a way that recapitulates the natural pattern. Our ISR data and proposed model (20) suggested that individual PFs experiencing regionally fluctuating stress and damage (and thus ISR activity) over time might reflect a situation analogous to a random walk (RW; 32, 33) relative to a threshold of growth activation (Fig. ib).…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations